OVERVIEW OF PATIENTS WITH CHRONIC RHINOSINUSITIS UNDERGOING SURGERY IN PADANG, WEST SUMATRA, 2018-2022 - Irfandy, Dolly; Handayani, Tuti; Budiman, Bestari Jaka; Megananda, Cahaya (Universitas Airlangga, 2024)
Introduction: Chronic rhinosinusitis (CRS) remains a health problem that affects the quality of life of patients and often requires surgery. Approximately >60% of CRS patients undergo surgery. Aims: This study aims to identify an overview of patients with chronic rhinosinusitis undergoing surgery in Padang, West Sumatra, 2018-2022. Methods: This type of study is a descriptive observational study conducted by observing the medical records of CRS patients at the ENT-HNS Outpatient Department of RSUP Dr. M. Djamil Padang for the period January 2018 – December 2022 with a total sample of 138 patients. Samples were collected using a total sampling technique and then analyzed univariately. Results: The results of this study showed that CRS patients were found mostly (21.7% each) in the 41-50 years and 51-60 years age groups, more than half (52.2%) were male, and most (86.2%) lived in West Sumatra area. Most (89.9%) patients presented with nasal congestion and more than half (55.1%) had CRSwNP. Staphylococcus epidermidis was the most common microbe type (29.8%) found in patients. Most total Lund-Mackay scores (24.6%) were found in the 5-8 score range. Most (83.3%) patients visited postoperatively for ≤ 3 months with an average of 3.6 visits per patient. Conclusion: This study provides an overview of CRS patients who underwent surgery, which is crucial for determining the most appropriate management strategies to prevent the worsening of patient symptoms. Furthermore, this study may provide an overview of the duration of post-sinus surgery control.